Contested pasts : the politics of memory - Hodgkin, Katharine, 1961-; Radstone, Susannah (London ; New York : Routledge, 2003)
This inter-disciplinary volume demonstrates, from a range of perspectives, the complex cultural work and struggles over meaning that lie at the heart of what we call memory.
Introduction: Contested pasts / Katharine Hodgkin and Susannah Radstone -- Transforming memory -- The massacre at the Fosse Ardeatine: history, myth, ritual and symbol / Alessandro Portelli -- Memories and histories, public and private: after the Finnish Civil War / Anne Heimo and Ulla-Maija Peltonen -- War, history, and the education of (Canadian) memory / Graham Carr -- 'We would never have come without you': generations of nostalgia / Marianne Hirsch and Leo Spitzer -- Remembering suffering: trauma and history -- The traumatic paradox: autobiographical documentary and the psychology of memory / Janet Walker -- Memories of violence in interviews with Basque nationalist women / Carrie Hamilton -- Sale of the century? Memory and historical consciousness in Australia / Paula Hamilton -- 'Brothers and sisters, do not be afraid of me': trauma, history and the therapeutic imagination in the new South Africa / Christopher J. Colvin -- Patterning the national past -- Nationalism and memory at the Tuol Sleng Museum of Genocide Crimes, Phnom Penh, Cambodia / Rachel Hughes -- The death of socialism and the afterlife of its monuments: making and marketing the past in Budapest's Statue Park Museum / Maya Nadkarni -- From contested to consensual memory: the Rock and Roll Hall of Fame and Museum / Robert Burgoyne -- 'Dead Man': film, colonialism, and memory / Chris Healy -- And then silence ... -- Memories between silence and oblivion / Luisa Passerini.
Includes bibliographical references and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Memory -- Social aspects; Memory -- Political aspects; Memory; History; Recollection (Psychology); Memory; History; Mental Recall; Mémoire.; Histoire; Rappel (Psychologie); history (discipline); memory (psychological concept); SELF-HELP -- Personal Growth -- Memory Improvement; Recollection (Psychology); Memory; History; Memory -- Political aspects; Memory -- Social aspects